Predictive Factors of Outcomes in Helmet Therapy for Deformational Plagiocephaly and Brachycephaly. Issue 1 (10th January 2023) - Hauc, Sacha C.; Long, Aaron S.; Rivera, Jean Carlo; Ihnat, Jacqueline; Littlefield, Timothy R.; Shah, Hemali P.; Pondugula, Nishita; Junn, Adam H.; Almeida, Mariana N.; Alper, David; Persing, John; Alperovich, Michael
Abstract : Deformational plagiocephaly and brachycephaly, or abnormal flattening of the infant skull due to external forces, are often managed with orthotic helmet therapy. Although helmet therapy is widely used, the factors that predict poor outcomes are not well characterized. In this study of over 140, 000 patients who received helmet therapy, older age and greater severity at presentation, and noncompliance with treatment were each independently associated with worse craniometric and provider-reported outcomes. Each additional point of cranial vault asymmetry index or cephalic index at a presentation is associated with an increased likelihood of residual brachycephaly at completion [odds ratio (OR): 1.067; 95% Cl: 1.058–1.075; P <0.0001 and OR: 2.043; 95% CI: 2.021–2.065; P <0.0001, respectively], whereas each additional point of cranial vault asymmetry index at a presentation associated with increased likelihood of residual asymmetry at completion (OR: 2.148; 95% Cl: 2.118–2.179; P <0.0001). Patients were more likely to have residual brachycephaly or asymmetry with increasing age at treatment initiation (OR: 1.562; 95% CI: 1.524–1.600; P <0.0001 and OR: 1.673; 95% Cl: 1.634–1.713; P <0.0001, respectively, for each additional month of age at initiation). These results highlight a need for prompt referral for helmeting, especially in cases with severe features or when patients present late to care. Potentially modifiable factors are age at helmeting and compliance with treatment protocols, and consideration of these factors may be important for achieving success in some cases.